Readability of sustainability Reports: Study on European and Asian companies - Kumar, Sandeep (2009)
Corporate social responsibility and sustainability reporting are gaining increasing importance globally as stakeholder concerns have expanded beyond conventional financial considerations to matters such as safety and health, as well as the impact of businesses on the environment and the community. This study focuses on the readability of sustainability reports. Forty companies from four different industries within European and Asian regions were selected. Passages from social performance section of their reports were then analysed using four different readability measures like Flesch reading ease, Flesh-Kincaid formula, Fog index and SMOG index. The objective of the study was: first, to find if the current sustainability reports readable? Second, which regions sustainability reports are more readable? And finally whether there is any relationship between readability of sustainability reports and companies financial performance. It was found during the study that social performance section of current sustainability reports from Europe and Asia regions are difficult to read. That means audience of these reports must have at least undergraduate level education for full comprehension. Among these two geographical regions, European sustainability reports are having better readability and comprehension than Asian. Lastly, neither positive nor negative relationship was determined between company’s financial performance and readability level of its sustainability report.